Endoscopic resection for gastric submucosal tumors: Japanese multicenter retrospective study. Issue 2 (9th November 2022) - Shichijo, Satoki; Abe, Nobutsugu; Takeuchi, Hirohisa; Ohata, Ken; Minato, Yohei; Hashiguchi, Kazutoshi; Hirasawa, Kingo; Kayaba, Shoichi; Shinkai, Hirohiko; Kobara, Hideki; Yamashina, Takeshi; Ishida, Tsukasa; et al.
Abstract : Objectives: Limited information is available on the efficacy and safety of endoscopic resection (ER) of gastric submucosal tumors (SMTs) in Japanese endoscopic practice where ER for gastric tumors is extremely popular. Methods: We conducted this study to elucidate the current scenario of ER for gastric SMTs in Japanese endoscopic practice. Patients (from 12 institutions) with gastric SMTs who underwent ER were enrolled from the first case until August 2020. Results: We enrolled 117 patients with 118 lesions. The number of patients who underwent ER increased over the years. The mean endoscopic tumor size was 20 ± 7.2 (8–40) mm. The growth type was primarily intraluminal (90%). The mean resection and wound closure times were 58 ± 38 (range, 12–254) min and 31 ± 41 (range, 3–330) min, respectively. Complete ER was achieved for 117 (99%) lesions. Full‐thickness resection rate was 44%; however, only 12 (10%) patients required abdominal paracentesis for decompression. Endoscopic treatments were completed in 115 (97%) lesions, while three lesions required conversions to laparoscopic surgery due to luminal collapse, uncontrolled bleeding, and difficulty in defect closure. Gastrointestinal stromal tumors were the most common pathology (74%). No recurrence was observed during the mean follow‐up period of 4.3 ± 2.9 years. The 5‐year overall survival rate was 98.9% (95% confidence interval 97.8–100%). Conclusion: Performance of ER for gastric SMTs is increasing in Japan. The technique seems feasible in Japanese endoscopic practice, warranting further validation in a prospective study.